Approaches to studying teacher collaboration for instructional improvement: A review of literature. (February 2022) - Weddle, Hayley
Abstract: While prior literature reviews provide insights into the characteristics and outcomes of teacher collaboration, they minimally address the theories and methods undergirding studies. However, these factors profoundly shape research, including how meaning is drawn from findings. Foregrounding theory and methods, this review examines approaches to studying teacher collaboration for instructional improvement. The 43 reviewed publications illustrate that while research on teacher collaboration is methodologically robust and often theoretically grounded, the use of interdisciplinary and critical theories could expand knowledge on collaboration as a pathway for transformation. Findings also illuminate the need for additional longitudinal research as well as studies with a focus on contextual factors such as school funding, size, and student demographics. Such work could inform how productive collaboration can be supported across a range of school contexts.